Nostalgiczna podróż Petra Zoranicia po „mapie wspomnień” - Antonina, Divna Mrdeža (Slavia Occidentalis, 2015)
Zoranić built the problem of geopolitical and real time and space in his highly complex literary work through the use of genre. The work is constructed based on of Sannazzaro’s Arcadia, inspired by Ovid’s Metamorphoses and Dante’s Inferno, with an epistemological framework dedicated to Matijević and written according to the style and philosophy of Petrarch and the national folklore of love poems. In addition, the importance of literature in an existentially threatened community is strictly related to the dichotomy of the epistemology of the appraisal of poetry as present from the pre-Platonic epoch to Zoranić’s humanistic debates. Zoranić speaks in favour of the poet as a medium of God (poeta theologus). Just like his models (especially Petrarch and Dante as supporters of studia humanitatis) he relies on church authorities (Saint Jerome, Augustine, Cassiodorus and Saint Isidore of Seville). Therefore, the author manages to capture in this poetical and cultural context the personal issues presented in literature (in Petrarch’s pastoral themes) as well as community-related issues (paradise and an existentially threatened community). As a result of a journey through shepherds’ retreats, the area of deželji that is at the same time Arcadia, the Avenue des Champs-Élysées and Paradise Lost, transforms into a wasteland. The destroyed cities and strongholds along the Krka canyon (the locus horridus as a symbol of the seized bašćina [fatherland]), down the river Krka from its source to the mouth (catharsis/ re-birth) are symbols of the young poet’s turning from personal literature (lyrical poetry) to serious anti-Ottoman literature, aimed at saving literature’s identity as well as the bašćinian. The description of the deserted land – a symbol of a historical martyr place – is a message about the community’s role as sacrificial lamb. The return to Nin (the pseudo-mythological oldest town in the bašćina) brings the search to an end, but as a return to the starting point of the individual and the community. Zoranić introduces an allegory to the end of Mountains (Planine): the farewell at the beautiful Jela’s grave in his native Nin is a literary farewell to Petrarch’s Donna, notwithstanding whether it is a girl or the poet’s mother. The author’s decision to deal with national issues is reflected in the shift from Jela’s grave to the celebration of the famous bašćinianina [grave] of Juraj Divnić.